1979
DOI: 10.1111/j.1532-5415.1979.tb06125.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Among Older Persons: Findings from a Western New York State General Population Survey

Abstract: This report on the drinking patterns of older persons is based upon a cross-sectional probability sample of 1,041 adults aged 18 years or older living in Erie and Niagara Counties in Western New York State. The rates of drinking, heavy drinking, and alcohol-related problems were considerably lower among persons aged 60 or older than among those aged 50--59 (approaching old age), or among those aged 18--49 (the younger comparison group). Although heavy drinking was almost nonexistent among the elderly women, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
39
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 16 publications
11
39
0
Order By: Relevance
“…Associations between retirement and late-onset AUD or heavy drinking Barnes (1979) found no significant relation between unemployment and alcohol consumption in the 60 + …”
Section: General Description Of Included Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Associations between retirement and late-onset AUD or heavy drinking Barnes (1979) found no significant relation between unemployment and alcohol consumption in the 60 + …”
Section: General Description Of Included Studiesmentioning
confidence: 89%
“…In a study of 200 heavy drinking participants above the age of 60, Barnes (1979) found that only 3% of those who were widowed were heavy drinkers, whereas as many as 10% of those who were still married and above age 60 were heavy drinkers. He concluded that there was no significant relation between widowhood and heavy drinking, but did not report any statistical tests and gave no values for this non-significance.…”
Section: Associations Between Death Of Spouse and Late-onset Aud Or Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also observed that the stresses of ageing, such as widowhood and retirement, are not associated with increased problem drinking [28]. A study of 2641 community-dwelling non-disabled people aged 65 years and over registered at a general practice in London found that after adjustment for age, sex, income, and educational attainment, living alone was associated with multiple falls, functional impairment, poor diet, smoking status, risk of social isolation, but not hazardous alcohol use [29].…”
Section: Alcohol and Well-beingmentioning
confidence: 99%
“…Many cross-sectional studies, encompassing broad age ranges, have shown an association between older age and lower alcohol consumption and levels of drinking problems (Barnes, 1979;Breslow and Smothers, 2004;Dawson et al, 1995;Eigenbrodt et al, 2001;Johnson et al, 1998;Knupfer and Room, 1964;Livingston and Room, 2009). Longitudinal studies also have generally shown that older age predicts lower alcohol consumption as well as faster decline in alcohol use and drinking problems (Glynn et al, 1985;Karlamangla et al, 2006;Levenson et al, 1998;Moore et al, 2005; but see Kerr et al, 2004).…”
Section: Change In Alcohol Consumption and Drinking Problems With Agementioning
confidence: 99%